Early Maternal Employment and Children's Vocabulary and Inductive Reasoning Ability: A Dynamic Approach. Issue 2 (6th April 2017) - Kühhirt, Michael; Klein, Markus
Abstract : This study investigates the relationship between early maternal employment history and children's vocabulary and inductive reasoning ability at age 5, drawing on longitudinal information on 2, 200 children from the Growing Up in Scotland data. Prior research rarely addresses dynamics in maternal employment and the methodological ramifications of time‐variant confounding. The present study proposes various measures to capture duration, timing, and stability of early maternal employment and uses inverse probability of treatment weighting to control for time‐variant confounders that may partially mediate the effect of maternal employment on cognitive scores. The findings suggest only modest differences in the above ability measures between children who have been exposed to very different patterns of eary maternal employment, but with similar observed covariate history.